Geochemical characterization of waste rock dump and its potential to predict acid mine drainage - J.K. Kusi; G. Foli; M.Y. Peasah; O. Akoto (Scientific African)
Acid Mine Drainage (AMD) is an environmental phenomenon that is being experienced by mining companies in Ghana. High levels of heavy metals have been reported in mining areas especially in Obuasi over the years; however, as to whether these heavy metals are being released from the mine wastes (waste rocks) is of concern. Therefore, this paper evaluates the potential of the abandoned Anyankyirem waste rock dump located in Obuasi to cause AMD. Twenty rock samples were collected from various locations of the dump site and their elemental and physicochemical compositions were examined. XRD analysis was conducted to assess the mineralogy of the samples. Acid Base Accounting (ABA) test was used to ascertain the AMD potential of the dump. The ABA test comprises calculating the Acid Neutralization Capacity (ANC) and Maximum Potential Acidity (MPA) of the various samples. The MPA and ANC values were used to compute the rock samples' Net Neutralization Potential (NNP). A column leaching test was carried out. Leachates were collected over a period of 20 weeks. From the column leaching experiment, the rate of weathering of calcium carbonate throughout the 20-week leaching experiment was 3.6 %. Leachates from the column test showed a circumneutral pH (7.1–8.0). The sulphate concentrations from the leachates decreased over the entire period from 96.60 to 3.70 mg/L. Iron recorded the highest concentration of 7783.65 mg kg-1 and the lowest of 0.645 mg kg-1 was recorded in Bi. From ABA test and the column leaching test results, Anyankyirem waste rock dump is not acid generating and therefore can serve as buffer for high pyrite waste rocks. However, significant levels of some heavy metals (As, Fe, Zn, Cr, Mn and Se) were recorded in the leachates even though the leachates’ pH were circumneutral. The results suggest that not only acidic conditions can leach out heavy metals.